Drug-protein binding ([Place of publication not identifed] : New York Academy of Sciences, 1973)
The objective of this conference is to carefully review and appraise the salient studies that form the basis of our knowledge of this subject.
Drug-protein binding /, Drug
Keywords: PHARMACOLOGY